Toddlers' Processing of Phonological Alternations: Early Compensation for Assimilation in English and French. Issue 1 (9th September 2012) - Skoruppa, Katrin; Mani, Nivedita; Peperkamp, Sharon
<x xml:space="preserve">Abstract</x> Using a picture pointing task, this study examines toddlers' processing of phonological alternations that trigger sound changes in connected speech. Three experiments investigate whether 2;5‐ to 3‐year‐old children take into account assimilations—processes by which phonological features of one sound spread to adjacent sounds—for the purpose of word recognition (e.g., in English, ten pounds can be produced as te[mp]ounds). English toddlers (n = 18) show sensitivity to native place assimilations during lexical access in Experiment 1. Likewise, French toddlers (n = 27) compensate for French voicing assimilations in Experiment 2. However, French toddlers (n = 27) do not take into account a hypothetical non‐native place assimilation rule in Experiment 3, suggesting that compensation for assimilation is already language specific.